The Strengths and Pitfalls of Google Classroom Application to Gen-Z Students’ Learning Hybridity - Mualim, Maulana; Ma’rufah, Desi Wijayanti; Sartika, Endang (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Inarguably, learning and teaching activities should go hand in hand with the development of socio-cultural changes of the students. In the current circumstance, learning should not be any more carried out through a mere physical activities in classrooms, digital technology that has been occupying the Gen-Z students’ lives is highly suggested to be utilized as part of the teaching activities. This descriptive study seeks to address the strengths and pitfalls of Google Classroom application to reading and writing classes that the Gen-Z students encounter in the IAIN Purwokerto context. The purposive sample of this study is the second year students of Tadris Bahasa Inggris major who take reading and writing classes. The data, which are generated through questionnaire and interview methods of collection, are presented in a descriptive report showing the students’ perception on the hybrid learning activities imposed to them.